QUADAS-2: a revised tool for the quality assessment of diagnostic accuracy studies - Whiting, Penny F; Rutjes, Anne W S; Westwood, Marie E; Mallett, Susan; Deeks, Jonathan J; Reitsma, Johannes B; Leeflang, Mariska M G; Sterne, Jonathan A C; Bossuyt, Patrick M M (Annals of internal medicine, 2011)
In 2003, the QUADAS tool for systematic reviews of diagnostic accuracy studies was developed. Experience, anecdotal reports, and feedback suggested areas for improvement; therefore, QUADAS-2 was developed. This tool comprises 4 domains: patient selection, index test, reference standard, and flow and timing. Each domain is assessed in terms of risk of bias, and the first 3 domains are also assessed in terms of concerns regarding applicability. Signalling questions are included to help judge risk of bias. The QUADAS-2 tool is applied in 4 phases: summarize the review question, tailor the tool and produce review-specific guidance, construct a flow diagram for the primary study, and judge bias and applicability. This tool will allow for more transparent rating of bias and applicability of primary diagnostic accuracy studies.